Effects of self-relevant cues and cue valence on autobiographical memory specificity in dysphoria. Issue 3 (3rd April 2017) - Matsumoto, Noboru; Mochizuki, Satoshi
ABSTRACT: Reduced autobiographical memory specificity (rAMS) is a characteristic memory bias observed in depression. To corroborate the capture hypothesis in the CaRFAX (capture and rumination, functional avoidance, executive capacity and control) model, we investigated the effects of self-relevant cues and cue valence on rAMS using an adapted Autobiographical Memory Test conducted with a nonclinical population. Hierarchical linear modelling indicated that the main effects of depression and self-relevant cues elicited rAMS. Moreover, the three-way interaction among valence, self-relevance, and depression scores was significant. A simple slope test revealed that dysphoric participants experienced rAMS in response to highly self-relevant positive cues and low self-relevant negative cues. These results partially supported the capture hypothesis in nonclinical dysphoria. It is important to consider cue valence in future studies examining the capture hypothesis.